Transcriptome analysis reveals the proline metabolic pathway and its potential regulation TF-hub genes in salt-stressed potato - Jing, Quankai; Hou, Hualan; Meng, Xiaoke; Chen, Airu; Wang, Lixia; Zhu, Husen; Zheng, Shuang; Lv, Zhaoyan; Zhu, Xiaobiao (Frontiers in Plant Science, 2022)
Potato (Solanum tuberosum) is currently the third most important food crop in the world. However, the production of potato is seriously threatened by salt stress, which often occurs in the facility cultivation environment, and the mining of salt tolerance genes in potato remains to be further studied. In this study, test-tube plantlets of DM potato were treated with 200-mM NaCl to simulate salt stress, and 15 cDNA libraries were constructed for RNA-seq analysis. A total of 8383 DEGs were identified, of which 3961 DEGs were shared among all the salt treatments, and 264 (7.15%) TF-coding genes were identified from these shared DEGs. KEGG enrichment analysis showed that most DEGs identified from the “arginine and proline metabolism” (ko00330) were enriched in the proline metabolic pathway, and their functions almost covered the whole proline metabolic process. Further analysis showed that expression levels of all the 13 structural DEGs in the pathway were significantly up-regulated and proline accumulation was also significantly increased under salt stress, and 13 TF-hub genes were discovered by WGCNA in the lightcyan and tan modules which were highly positively correlated with the proline contents. Correlation analysis revealed that the four TF-hub genes of the lightcyan module and seven structural DEGs of the proline metabolic pathway might be the potential candidate genes, especially the potential and novel regulatory gene StGLK014720. Furthermore, the dual-luciferase reporter assay confirmed that the key protein StGLK014720 could activate the promoters of both structural genes StAST021010 and StAST017480. In conclusion, these results lay the foundation for further study on the salt tolerance mechanism of potato, and provide a theoretical basis and new genetic resources for salt tolerance breeding of potato.